The Effect of Changes in Ignition Timing on Power, Torque and Fuel Consumption on the Honda Supra X 125CC - Wagino, Wagino; Jalinus, Nizwardi; Refdinal, Refdinal; Nanda, Iffarial; Firdaus, Jeri Rizal (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the effect of changes in ignition timing on power, torque and fuel consumption on a Honda Supra X 125 CC. This study used an experimental research method. The object of this research is a motorcycle Supra X 125 CC that uses premium fuel RON 88, pertalite RON 90 and pertamax RON 92 with a standard ignition time of 15 ° before TDC, 16 ° before TDC and 17 ° before TDC. The research instruments used were a chassis dynamometer, timing light, fuel meter and a stopwatch. Data analysis using descriptive method. Based on the results of the study it can be concluded that the use of pertalite fuel with a change in ignition time of 17 ° before TDC can increase the power at 9.87 HP, up by 1.25%, torque at 1.18 kgf / m or an increase of 1.70% and fuel consumption increases as the time / angle of ignition advances.